FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM PADA PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rudi Setiadi Tjahjono (Jurnal Bisnis dan Akuntansi, 2013)
The objective of this research is to provide empirical evidence of dividend yield, price earnings ratio, market to book ratio, return on assets, debt to equity ratio, earnings per share and current ratio towards stockreturn. This research used data that were taken from non financial companies listed in Indonesian Stock Exchange over three years period 2010 until 2012. This research used purposive sampling method. The samples of this research consist of 90 companies that meet the criteria. This research uses multiple regression analysis. The result of the research showed that return on assets and debt to equity ratio had significant influence towards stock return while dividend yield, price earnings ratio, market to book ratio, earnings per share and current ratio had no influence.